Determinant factor influencing financial performance LQ45 corporation - Neni Meidawati; Reny Lia Riantika; Reiga Farah Amalia (Faculty of Economics, Universitas Islam Indonesia, 2020)
The aim of this research is analyzing factors which influence corporation performance in Sharia-based firms by using independent variables, such as Corporate Social Responsibility Disclosure and Indonesia Sharia Stock Index (ISSI) Listing, and Corporation Financial Performance as dependent variable. Data which being used was secondary data consisting CSR disclosure information from annual financial report from the listed corporation in LQ45 Index and Indonesia Sharia Stock Index (ISSI) within the period of 2016-2018. Data analysis used Multiple Linear Regression. The result of this research showed that Corporate Social Responsibility and Indonesia Sharia Stock Index (ISSI) Listing’s disclosure had negative effect towards Corporation Financial Performance.